2004
DOI: 10.1136/jcp.2004.017475
|View full text |Cite
|
Sign up to set email alerts
|

A case of 49,XXXXX in which the extra X chromosomes were maternal in origin

Abstract: This report describes an 11 month old female baby with features of pentasomy X. A molecular and cytogenetic evaluation revealed that her karyotype was 49,XXXXX and her extra X chromosomes were of maternal origin. She has muscular hypotonia, mental retardation, a cleft palate, mild hydrocephalus as a result of dilatation of both lateral ventricles, hyperextensible elbow joints, proximal radioulnar synostosis, clinodactyly of the fifth finger, valgus of the feet, and small hands and feet. In addition, she has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 7 publications
1
22
2
Order By: Relevance
“…In general, this aneuploid state arises as a result of meiotic malfunction, either maternal or combined maternal and paternal in origin. The most likely mechanism is nondisjunction of maternal X chromosomes in both divisions of meiosis to produce a tetrasome X ovum, and this hypothesis has been supported by molecular analysis of X-linked polymorphic markers [5] . DNA microsatellite analysis in our study showed that the extra X chromosomes were maternal in origin, probably as a result of successive sequential nondisjunctions in meiosis I and II of oogenesis, involving both chromatid pairs in meiosis II.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In general, this aneuploid state arises as a result of meiotic malfunction, either maternal or combined maternal and paternal in origin. The most likely mechanism is nondisjunction of maternal X chromosomes in both divisions of meiosis to produce a tetrasome X ovum, and this hypothesis has been supported by molecular analysis of X-linked polymorphic markers [5] . DNA microsatellite analysis in our study showed that the extra X chromosomes were maternal in origin, probably as a result of successive sequential nondisjunctions in meiosis I and II of oogenesis, involving both chromatid pairs in meiosis II.…”
Section: Discussionmentioning
confidence: 77%
“…Although many studies of numerical and structural chromosome abnormalities in fetuses following ICSI have been published, most of those pregnancies were found to involve sex chromosomes [1,2] , predominantly of paternal origin [2,3,5] . However, maternal-derived autosomal trisomy 18, 21 and monosomy 21 were also reported [2,3] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 25% of cases, this malformation is genetically conditioned [7]. Congenital radioulnar synostosis is also one of many components of malformation syndromes in children with chromosomal aberrations [8,9]. It is commonly believed that this malformation is connected with chromosome X aberrations [10].…”
Section: Introductionmentioning
confidence: 99%